Postoperative pain in children: a gender approach - Moura, Louise Amália de; Oliveira, Ana Carolina D'Arelli de; Pereira, Gilberto de Araújo; Pereira, Lílian Varanda (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to verify and describe, from a gender focus, the associations between gender and specific postoperative pain variables in pediatrics. This is a cross-sectional study of 77 children between 6 and 13 years of age (M=9 years; sd=2.2 years), ASA I and II, 77.9% from low-income classes, 68.8% boys and 32.8% girls. Data were collected on the first postoperative (1st PO) day through semi-structured interviews and four measurement scales. The main baseline diseases were adenotonsillitis and fractures. Prevalence of pain on the 1st PO was 91.7% for girls and 75.5% for boys (p>;0.05). No association was found between pain intensity and gender. The most used pain descriptors were it cuts and it squeezes. The preferred scale was the EFMC (with faces from a Brazilian cartoon: Monica's Gang). Pediatric pain management is still inadequate and gender may influence the pain response.